СОЦИАЛЬНАЯ СРЕДА И ЧЕЛОВЕЧЕСКАЯ СУДЬБА В РАННИХ ТРАГЕДИЯХ ГУСЕЙНА ДЖАВИДА (Journal of Oriental Studies, 2016)
Аса көрнекті романтик-ақын Гусейн ДжавидАзербайжан әдебиетіне ұлы трагик ретінде енді.Джалил Мамедкулизаденің «Чайный сервиз» атты бірактілі өлеңмен жазылған пьесасы бола тұрса да,әдебиетшілерГ. Джавидті өлеңмен жазылған драманың негізінсалушы ретінде санайды. Мақала Г. Джавидтің ерте-ректе жазылған трагедияларындағы әлеуметтік ортамен адам тағдыры туралы.The article deals with the early tragedies of the knownplaywright and the poet of Azerbaijan – H.Javid, whichdiffer depth of philosophical thought and are classics of theAzerbaijan literature. H. Javid's tragedies- "The Satan", "Maral", "Lame Timur" differ art expression of ideas ofhumanism. The philosophical and ethical position of theauthor in the approach to a theme in "Mother" which baseda genre of poetic tragedy in the Azerbaijan dramatic art is inthis respect rather significant.